STUDY OF AUTOMATIC DEM (DIGITAL ELEVATION MODEL) PROCEDURE USING SATELLITE IMAGES OF PLEIADES (CASE STUDY OF BANDUNG - WEST JAVA) - Aryani, Dian Ika (Jurnal Pendidikan Geografi Gea, 2017)
The topographic maps can be derived from Digital Elevation Model (DEM), which can be obtained from satellite imagery data extraction. This result might be achieved by using a Very High-Resolution Satellites (VHRS) Imagery, such as Pleiades Satellite. The main objective of this research is to review the procedures of Automatic DEM Extraction in order to obtain minimum error. The systematic implementations of this research are modeling the sensor, generating automatic tie point and performing automatic DEM extraction. The results of DEM extraction can be either point cloud data or mesh data which are verified by comparing the reference data. This is lead to acquire pairing combination of Pleiades imagery data which has the smallest error value among all of them. The comparison showed that the tri stereo pairing combination of the DEM extraction model has a lower accuracy than the backward â nadir pairing combination.